The Influence of The SCL Model and Mind Mapping Learning Media on Learning Outcomes Through Motivation - Suhariami, Yuyun; Sri Hariani, Lilik; Sulistyo, Sulistyo (Abjadia : International Journal of Education, 2026)
This study aims to analyze the influence of the SCL model and Mind Mapping learning media on student learning outcomes in the IPAS subject through learning motivation. The background of this research is based on the low student achievement at MI Mambaul Ulum Karangduren, which is caused by limited learning independency and low motivation. The SCL model is considered capable of encouraging student activeness and independency during the learning process, while Mind Mapping, as a visual learning medium, is expected to enhance concept understanding and learning interest. This study employed a quantitative approach. The population in this study was 75 fourth-grade students at MI Mambaul Ulum Karangduren for the 2024/2025 academic year, with a sample of 35 students. The data analysis technique used in this research included classical assumption testing, and hypothesis testing using path analysis to determine direct, indirect, and total effects among the variables. The results showed that both the SCL model and Mind Mapping media had a significant influence on learning motivation, which in turn affected the learning outcomes. Furthermore, there was an indirect effect of the SCL model on learning outcomes through motivation, but no indirect effect was found for the Mind Mapping media through motivation. Therefore, there is a total effect of the SCL model and Mind Mapping media on learning outcomes through learning motivation. These findings confirm that the combination of a student-centered learning model and engaging visual media can effectively improve student motivation and academic performance. However, this study is limited by its specific geographical scope at a single institution and does not measure the long-term effectiveness of these models beyond the current academic term.